Pengukuran Kinerja Billing System menggunakan COBIT Framework dan Computer Assist Audit Technique (CAAT) Pada Grand Mutiara Hotel Pangkalpinang - Riani Riani; Darus Altin (Journal of Accountancy, 2013)
The use in information technology aims to get precision and accuracy in recording all sales activities so that eventually led to a financial statement which is expected to provide information that is free of errors. To avoid errors in the present information matters played an important role is the management of data. Management off good data in addition to avoid errors as well reduce the risk of data loss, such as damage, error or theft of the parties which is not desired. This research aims to determine the extent to wich performance of the billing system in Grand Mutiara Hotel, particularly in the management of the data with the COBIT framework approach and find out whether the accounting data processing based on testing Computer already accurately assists Audit Techniques (CAAT). Draft research is descritive by approach case study. The kind of data used are qualitative. Objects in this research is Grand Mutiara Hotel Pangkalpinang. Data obtained from internal resources, namely related parties, with billing system. Data is obtained by way of spreading a questionnaire, conduct an interview and observation directly. The research results showed that perrformance of the billing system in Grand Mutiara Hotel, particularly in the managemen of data (DS11) with the COBIT framework approach based on the value of maturity (maturity level) provides present performance results (as is) at the level of repeatable, as for the expected performance (to be) is an optimized level. While the accounting data proccesing based on testing Computer assists the Audit techniques-CAAT (Commputer assist Audit Techniques- TABK) isun accurate